Works for Works, Book 1: Useless Beauty - Gavin Keeney (punctum books, 2022)
Works for Works, Book 1: Useless Beauty tackles "legacy" issues of intellectual property rights (IPR) in artistic production and academic scholarship and proposes a category or class of works that has no relation to IPR nor to proprietary regimes of copyright and academic privilege. Keeney's book is a structuralist argument for establishing new forms of artistic scholarship that operate in direct opposition to established norms in both the art world and neoliberal academia, and is also rigorously contextualized within past and present-day arguments for and against patrimonial and paternalistic, avant-garde and normative, forms of censure and conformity across cultural production. Works for Works, Book 1: Useless Beauty privileges an iterative, generative, and aleatory methodology for artistic scholarship, with transmedia proposed as a "tutelary form" of editioning works against the dictates of the art-academic complex. This focus on generativity also invokes the dialectical operations historically associated with past avant-gardes as they have negotiated an elective nihilism as an avenue for exiting established and authorized forms of conceptual and intellectual inquiry in the Arts and Humanities.
Keywords: 300; academic freedom; copyright; intellectual property; legal studies; moral rights; political economy; preposterous presentism